HUBUNGAN ANTARA KOMPETENSI HUMAS PEMERINTAHAN PROVINSI JAWA BARAT DENGAN STANDARISASI PELAYANAN KEPADA MASYARAKAT - Prakasa, Sangra Juliano; Ismail, Oki Achmad (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2018)
This study aims to determine the extent of the relationship between the Competence of Public Relations Government of West Java Province which includes communication skills, managerial abilities, ability to build relationships, credibility and creativity, with Standardization of Services is measured through the Service Level Agreement concept which includes Accessibility, Reliability, Response Time, and Resolution who were given Public Relations to the Community who visited / visited the Public Relations Government of West Java Province. The method used is the Survey research method, through questionnaires to the people who came to the West Java Provincial Government Public Relations. The testing techniques carried out are frequency distribution tabulation, score ranking and correlation test. The results of the study illustrate that the Public Relations Government of West Java Province has communication and managerial skills in the Very good category, with the ability to foster relationships, credibility and creativity in the category of Good, Whereas the assessment of Standardization of Services to the Community is measured through Accessibility, reliability, response time and resolution in the category of Satisfaction. From the results of testing the correlation data, it can be concluded that There is a strong, unidirectional and significant relationship between PR competencies in West Java Province with the standardization of services to the public. A unidirectional relationship means that the West Java Provincial Government Public Relations Competency is good, Service Standardization also be more satisfying